Multiple food allergy. - Pinheiro, Adriana (2011)
Multiple food allergy is an adverse immune response to more than one food. When a child is allergic to a great number of foods, the clinical picture can be serious and the eviction of the implied allergens leads to important dietary restrictions. We describe the case of a 4-year-old child with serious atopic eczema and multiple food allergy. At 8 months she presented positive specific Imunoglobulin (Ig)E for milk, wheat, rye, barley, gluten, soy, egg (yolk and white) and initiated eviction of these foods. At 20 months she tried to introduce wheat but suspended after aggravation of atopic eczema. At 3 years old, she had anaphylaxis after contact with cheese. At 4 years old she keeps eviction of milk, egg, wheat, gluten, barley and rye. Food restrictions in these patients are high, demanding a rigorous control of foods ingested to prevent both adverse reactions and nutricional deficits. Multidisciplinary approach is important.